Analisis Pengaruh Green Banking Terhadap Profitabilitas Bank Umum Syariah Indonesia - Anggraini, Sindi; Muhammad Iqbal, Fasa (Journal of Business Management and Islamic Banking, 2022)
Research Aims: Islamic commercial banks are Islamic banks which in their activities provide services in payment traffic. Islamic commercial banks can operate as foreign exchange banks and non-foreign exchange banks. Foreign exchange bank is a bank that can carry out transactions abroad or related to foreign currencies as a whole, such as transfers abroad, collections abroad, opening letters of credit and so on. The purpose of the study was to determine the effect of green banking on the profitability of Islamic commercial banks in Indonesia and the concept of green banking in an Islamic perspective. Design/methodology/approach: This type of research is quantitative with a descriptive statistical approach, the research methodology used in this study is the method of documentation and literature study. Research Findings: The results of the study show that green banking has a positive effect on the profitability of Islamic Commercial Banks in Indonesia. In the Islamic perspective, all Green Banking Indicators are in accordance with the Islamic perspective as well as the reinforcing arguments about protecting nature and preventing natural damage. Keywords: Green Banking, profitibalitas, Bank Umum Syariah.